Il rapporto tra teoria e prassi nella supervisione. Formazione e ricerca dopo l’Analisi collettiva - De Simone, Gianfranco (Il sogno della farfalla, 2021)
The aim of this article is to deal with the rapport between supervision’s theory and practice. The author outlines the duties and limits in the therapist-patient supervision and examines some specific theoretical and therapeutical methodological models which identify in the unconscious dimension and early human relationship the etiopathogenetic factors of mental illness. The paper, drawing from the research on specific and non-specific therapeutic factors, analyzes the theoretical elements which lay the ground for a therapeutic practice able to comprehend how transformative events occur in order to be able to foresee and stimulate them. Massimo Fagioli’s Theory of Birth has been experimented through a psychotherapeutic process in a large group which was uninterruptedly carried out for forty years.